Dinamika Bullying di Sekolah: Faktor dan Dampak - Febrianti, Rizka; Syaputra, Yogi Damai; Oktara, Tri Windi (Indonesian Journal of Educational Counseling, 2024)
The problem of bullying has become a serious concern which has a psychological and emotional impact on teenagers. These include mental health problems, low self-esteem, social isolation, and even the potential risk of dangerous behavior. Based on this, this article aims to understand the dynamics of bullying in adolescents regarding the factors involved, the extent of its impact, and how society and the authorities or counselors can overcome this problem. This article uses a library research method that focuses on empirical research indexed by Google Scholar regarding the dynamics of bullying among teenagers in the last 5 years (2019-2023). In this literature review, 20 articles related to the dynamics of bullying in adolescents were identified, including factor aspects (11 articles) and impact aspects (9 articles). Research conducted in a variety of social contexts, such as school, online, or community settings, will be included in this analysis. The research results briefly show that there are factors that influence bullying behavior, including individuals, families, peers, the school environment, and the mass media. These factors play an important role in bullying behavior which has an impact on teenagers such as emotional problems including stress, depression, isolation and thoughts of suicide. Bullying can occur in various forms, including conventional (offline) and cyberbullying (online). Treatment and prevention efforts involve adolescents, families, schools and communities in building values, effective communication, prevention programs and social interventions. All parties need to play an active role in overcoming the problem of bullying.